Dispersion Modeling of SO2 and NOX from Transportation Sources Using Gaussian Model on Krikilan Highway, Driyorejo, Gresik - Wanda Anggraeni; Rachmanu Eko Handriyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
The emissions from transportation sources contribute to 70% of air pollutants. The increase in the number of vehicles results in traffic density and the production of pollutants. This research was conducted on Krikilan Highway on Mondays and Sundays during peak morning and afternoon hours for one month. Direct measurements were taken at distances of 0 m and receptors at 200 m, 400 m, and 800 m. The objective of this study is to assess the ambient air quality status, determine the results of direct measurements, Gaussian modeling, and the dispersion of SO2 and NOx gases generated by vehicles on the road. The ambient air quality measurements on Krikilan Highway, Driyorejo Subdistrict, showed the highest concentrations for SO2 at 34.03 µg/m3 and NOx at 120.41 µg/m3 on Sundays. The Gaussian model calculations on Krikilan Highway, Driyorejo Subdistrict, revealed the highest concentrations for SO2 at 0.00000262 µg/m3 and NOx at 0.0000787 µg/m3 at a receptor distance of 200 m on Mondays. The ambient air concentrations of SO2 and NOx on Krikilan Highway, Driyorejo, using Gaussian model calculations and measurements, complied with the standards set by Regulation No. 22 of 2021. The Index of Agreement (IOA) validation for SO2 and NOx concentrations yielded a value of 0.97.